Pengaruh Motivasi Berprestasi Dan Komunikasi Antar Pribadi Terhadap Prestasi Kerja Karyawan (Studi Pada PT. PG Rajawali I Surabaya) - Dwiarko Nugrohoseno, ; Harun Charismaini, (Bisnis dan Manajemen, 2008)
The organization always had changed phisicly or non phisicly. As PT. PG Rajawali I who the first time the system based on operating holding management transform be investmen holding and make high and low Achievement motivation,  Interpersonal Communication  and Performance Appresial. The aim of the research is for to know the influent Achievement Motivation and interpersonal Communication for performance Appresial and how to know what is Achievement Motivation to influent alike the dominant Performan Appresial.The research did do like a quantity with all of the employed population PT. PG Rajawali I amount of 90. Totally sample have used 73 employed. Instrument have been usedas tools collection file is quisioner amount of 13 items for X1 and 20 items for X2¬ and Y variabel used sekunder file from PT. PG Rajawali ITo test result of the hipotesis to show have a connection between variable Achievement Motivation and Interpersonal Comunication a like together with variable Performance Appresial. Coefficient correlation is 0,911 and regretion linier Y=-1,409+ 0,859X1+ 0,739X2. The determination correlation 0,830 mean of contribution variable Achievement Motivation and Interpersonal Communication with Perfomance Appresial is 83,00% and very dominant is Interpersonal Communication with correlation parsial X2= 0,649 more than big to compare with variable Achievement Motivation.